FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Setiawan Setiawan; Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of Return on Assets, Company Size, Debt to Equity Ratio, Current Ratio, and Company Age on Timeliness of Financial Reporting in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample taken using purposive sampling method and valid data are 57 companies. The data processing technique is logistic regression analysis using EVIEWS version 10 and Microsoft Excel 2010. The results of this study indicate that Return on Assets, Company Size, Debt to Equity Ratio, and Company Age have no significant effect on the timeliness of financial reporting. While the Current Ratio has a negative and significant effect on the timeliness of financial reporting. The implication of this research is that investors can pay attention to the timeliness of financial reporting in making investment decisions which can be seen through the value of Return on Assets, Company Size, Debt to Equity Ratio, Current Ratio, and Company Age.